Management of aseptic non-union of shaft femur using intramedullary nailing combined with bone grafting: a case report - Rengerla, Saikrishna B.; Lohkare, Akhil H.; Warade, Nikhil R.; Roy, Supratim; Wankhede, Aniket K. (International Journal of Research in Orthopaedics, 2022)
Despite the advances in trauma care, improved surgical techniques, latest implants and therefore the evolution of new adjuvants to healing, biologic agents, non-union still persists thanks to high energy trauma as initial event. Non-union of femur shaft represents a significant socioeconomic problem to the patient, related to prolonged patient morbidity, inability to return to figure, gait abnormality, re-operations and psycho-emotional impairment. Here we discuss the case of such non-union of fracture shaft femur presented to us with shortening of 3.5 cm managed with bone graft and intramedullary nailing. 22-year-old male patient had a history of trauma due to fall from bike due to dash from behind by tractor (high velocity road traffic accident) sustaining injury over right thigh leading to closed fracture mid-shaft femur of the same side treated immediately by femur nailing. After 6 months post-surgery, he noticed swelling over operated thigh which was increasing and causing difficulty in walking. X-rays revealed broken nail, re-operated at the same centre with dynamic compression plating (DCP) probably after freshening the fracture edges using 12-hole DCP, implant failure with whole plate and screw construct extrusion and re-fracture at the same site. This time patient presented to our institute. We planned of implant removal and intramedullary nailing with bone grafting. Management of aseptic femoral non-union with fracture gap of 2.5-4 cm range with intramedullary nailing combined with autologous fibular cortical and cancellous grafts showed good functional results at the end of 1 year post operative interval after prior repetitive failure of implants due to non-union.